LANGUAGE MANAGEMENT IN NON-MARRIAGE COUPLE - Alfi Sahri; Nurmalia Rafiana; Cut Droena Dibha (Universitas Islam Sumatera Utara (UISU), 2018)
This study aims to analyze how non-marriage couples plan language planning for their daily communicating and language decline for their future children when they are married. The population of this study is all couples dating arround Langsa as many as 10 couples. Data were collected using questionnaires for dating couples. The result of the research is that the coupleshas many good planning to plan the language fir them and their future child, beside that there are still many who want to use local language. Couples dating in the Langsa cuty prefer to plan language planning is the Indonesian language is the mother tongue and for their children will be able to easily communicate with people arround.